A saúde mental do intérprete de Libras em sua atuação no contexto remoto em tempos de pandemia - Silva, Suyene Pereira da (Universidade Federal de São Carlos, 2022)
This project aims to investigate the professional LIBRAS interpreter work and its specificities facing the remote context practice started during the COVID-19 pandemic, particularly between 2020 and 2021. This new kind of practice raised some concerns about the interpreter’s mental health, since before this work was mainly face-to-face. Thus, as a LIBRAS translator and interpreter in formation, who had the first experience in this context (since until then I had no experience with face-to-face work), through an autobiographical analysis of my field diary written during my college internship, I sought to present feelings and thoughts identified throughout the interpretations, aiming to discuss about the impacts of the remote context in my practice and my subjective perception about my activities as an interpreter. Perceptions were categorized through content analysis, and the results discussed and presented indicate that, although new tensions have emerged with remote context work - impacting, therefore, the mental health -, some positive aspects were also perceived, indicating that future researches could focus on the issue of mental health care in the LIBRAS interpreter and translator education, so that it considers remote context elements from now on, since apparently this work has expanded and it seems that it will remain even after the face-to-face work re-emerged.
The mental health of Libras interpreters in their work in the context remote in times of pandemic
Keywords: Saúde Mental; Tradutor e Intérprete de Libras; Atuação do TILS em Contexto Remoto; Mental Health; Libras Translator and Interpreter; Translator and Interpreter of Brazilian Sign Language in remote context; CIENCIAS HUMANAS